A study of effectiveness of optometric services provided by the mobile optometry clinic among people in UiTM Puncak Alam / Aisyah Mat Yacob - Mat Yacob, Aisyah (Faculty of Health Sciences, 2015)
Background: UiTM Mobile Optometry Clinic was introduced to serve the community with comprehensive and condusive eye screening program all over the Malaysia. Method: A descriptive survey study was conducted in UiTM Puncak Alam, as the birth place of Mobile Optometry Clinic to evaluate the effectiveness of the optometric services that being provided by the Mobile Optometry Clinic among the community in UiTM Puncak Alam that consist of students, staffs and social workers. Result: Majority of the respondents do think that the eye screening program is effective especially in detecting the eye-related problems. Other than that, optometry student’s skill is selected as main contributing factor together with its current location and schedule of the Mobile Optometry Clinic in UiTM Puncak Alam. While targeting the higher level of satisfaction of “very good”, most of them only felt the services provided is ‘good’. Conclusion: Media publication for UiTM’s community should be informed about the existence of the Mobile Optometry Clinic which is necessary to increase the future participation and quality of the determined contributing factors need to be improved for better eye screening’s outcome. Adjustment of the Mobile Optometry Clinic’s organization and physical surrounding can increase the rate of the patient’s comfort rate. h